Informed agitation : library and information skills in social justice movements and beyond - Morrone, Melissa (Sacramento, CA : Library Juice Press, 2014)
"Explores activist librarianship in the early 21st century"--
Introduction / Melissa Morrone -- In the city -- Documenting the untold stories of feminist activists at Welfare Rights Initiative: a digital oral history archive project / Cynthia Tobar -- threeSOURCE: reimagining ho we collect and share information about social issues / Jen Hoyer and Stephen MacDonald -- In the seminar -- Reading for a better future: Books for a Better Future (BFABF) and sustainability literacy in a U.K. public library / Dan Grace -- Teaching in the margins / Barbara A. Quarton -- In the struggle -- Knowledge my public library kept secret: the urgent need for culturally-responsive library service / Taneya D. Gethers -- Library programs and information access for women: a Canadian perspective / Moyra Lang and Gayle Sacuta -- In the archive -- Let's use what works: the radical archives of Philadelphia and traditional archive literature / Scott Ziegler -- "Less rent, more control!": creating an accessible archive for New York City's oldest tenants union / Maggie Schreiner -- In real life -- From Haiti to Miaim: security, serendipity, and social justice / Bâeatrice Colastin Skokan -- Inside and outside of the library: on removing barriers and connecting people with health care resources and zines / Jude Vachon -- In the movement -- Whatcha doin' after the demo?: The importance of archiving political posters / Vince Teetaert -- To spread the revolution: anarchist archives and libraries / Jessica Moran -- Building an archive from below: reflections from Interference Archive / Molly Fair -- In the community -- Queer Housing Nacional Google group: a librarian's documentation of a community-specific resource / Shawn(ta) Smith -- ÆCommunity: digital media, family heirlooms, and a global audience in the Lebanese in North Carolina Project / Caroline Olivia Muglia -- I the catalog -- Cutter & paste: a DIY guide for catalogers who don't know about zines and zine librarians who don't know about cataloging / Jenna Freedman and Rhonda Kauffman -- In the world -- Knowledge, access, and resistance: a conversation on Librarians and Archivists to Palestine / Vani Natarajan and Hannah Mermelstein -- In the streets -- Radical Reference: who cares? / Lia Friedman -- Librarian is my occupation: a history of the People's Library of Occupy Wall Street / Jaime Taylor and Zachary Loeb -- "Why archive?" and other important questions asked by Occupy Wall Street / Siãan Evans, Anna Perricci, and Amy Roberts -- Contributor biographies -- Index --
Bibliografske bilješke iza svakog rada. Kazalo.
Keywords: knjižnice - zagovaranje; knjižnice - politički aspekti; profesionalna etika; sloboda informiranja; intelektualne slobode